Impacto ambiental en la instalación de sistemas fotovoltaicos para electrificación rural en la cuenca de los Ríos Napo y Curaray, Loreto, 2024 - Chalco Guerra, Catherine Juana (2024)
It is a descriptive, cross-sectional and non-experimental study with the purpose of evaluating the environmental impacts of the installation of photovoltaic systems for electricity generation in the communities of the Napo and Curaray basins, in nine (09) communities in which monitoring of environmental parameters was carried out. Different measuring instruments with calibration certificates and in situ measurement were used to verify the status of the environmental parameters. For the analysis, descriptive statistics were used in order to summarize and contrast with the maximum limits allowed by the ECA of the national regulations, concluding that the installation of photovoltaic systems in the native communities of the Napo River has achieved a balance between providing access to renewable energy and minimizing the negative impacts on the environment and community health. Likewise, there is no significant relationship between the installation of photovoltaic systems and the changes observed in the environment and living conditions of rural communities, so the null hypothesis is accepted and the alternative is rejected. On the other hand, it is evident that the use of individualized and community photovoltaic systems is a replicable model for other areas with similar geographic and demographic characteristics in the Loreto región